The Body Across Adulthood: On the Relation Between Interoception and Body Representations - Raimo, Simona; Boccia, Maddalena; Di Vita, Antonella; Cropano, Maria; Guariglia, Cecilia; Grossi, Dario; Palermo, Liana (Frontiers in Neuroscience, 2021)
Interoceptive information plays a pivotal role in building body representations (BR), but the association between interoception and the different types of BR in healthy individuals has never been systematically investigated. Thus, this study aimed to explore the association between BR and interoceptive sensibility (IS) throughout adulthood. One hundred thirty-seven healthy participants (50 aged from 18 to 40 years old; 50 aged from 41 to 60 years old; and 37 over 60 years old) were given a self-report tool for assessing IS (the Self-Awareness Questionnaire; SAQ), and a specific battery including tasks evaluating three different BR (i.e., the body schema, using the Hand Laterality Task; the body structural representation, using the Frontal Body Evocation task, FBE; and body semantics, using the Object-Body Part Association Task) as well as control tasks (i.e., tasks with non-body stimuli). The older age group (aged over 60 years old) showed lower performances on the tasks probing the body schema and body structural representation than younger groups (aged 18 to 40 and 41 to 60 years old). More interestingly, worse performances on a task assessing the body schema were significantly associated with higher IS with older age, suggesting that higher awareness of one’s inner body sensations would decrease the plasticity of this BR. These findings are interpreted according to the neuropsychological model of BR development and the effects of aging on the brain.